2019
DOI: 10.1371/journal.pone.0211736
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between macrophage migration inhibitory factor and autophagy in Helicobacter pylori-associated gastric carcinogenesis

Abstract: The role of macrophage migration inhibitory factor (MIF) and autophagy in gastric cancer is not clear. We determined H. pylori infection status of the subjects and investigated the expression of MIF and autophagy markers (Atg5, LC3A and LC3B) in human gastric tissue at baseline. Then H. pylori eradication was done for H. pylori positive patients and MIF and Atg5 levels were investigated on each follow-up for both H. pylori-eradicated and H. pylori negative patients. Baseline tissue mRNA expression of MIF, Atg5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…MIF was first discovered in the culture medium of active T lymphocytes and macrophages, and it mediates the innate and adaptive immune system to exert immune-regulatory functions [23]. Although recent studies have indicated that MIF is involved in the regulation of autophagy in tumor cells, its role is unclear [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…MIF was first discovered in the culture medium of active T lymphocytes and macrophages, and it mediates the innate and adaptive immune system to exert immune-regulatory functions [23]. Although recent studies have indicated that MIF is involved in the regulation of autophagy in tumor cells, its role is unclear [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The positive rate of the H . pylori (HP) in gastric cancer patients was positively correlated with the expression of macrophage migration inhibition factor (MIF) ( 59 ). The expression of Mif can promote cell transformation, tumor cell proliferation, and metastasis.…”
Section: Microorganisms Inflammation and Cancermentioning
confidence: 99%